Effectiveness of a mindfulness-based childbirth education pilot study on maternal self-efficacy and fear of childbirth - Byrne, J.; Hauck, Yvonne; Fisher, C.; Bayes, Sara; Schutze, R. (Wiley-Blackwell Publishing, Inc., 2013)
Introduction: This pilot study tested the feasibility and effectiveness of using Mindfulness-Based Childbirth Education (MBCE), a novel integration of mindfulness meditation and skills-based childbirth education, for mental health promotion with pregnant women. The MBCE protocol aimed to reduce fear of birth, anxiety, and stress and improve maternal self-efficacy. This pilot study also aimed to determine the acceptability and feasibility of the MBCE protocol. Methods: A single-arm pilot study of the MBCE intervention using a repeated-measures design was used to analyze data before and after the MBCE intervention to determine change trends with key outcome variables: mindfulness; depression, anxiety, and stress; childbirth self-efficacy; and fear of childbirth. Pregnant women (18-28 weeks’ gestation) and their support companions attended weekly MBCE group sessions over 8 weeks in an Australian community setting.Results: Of the 18 women who began and completed the intervention, missing data allowed for complete data from12 participants to be analyzed. Statistically significant improvements and large effect sizes were observed for childbirth self-efficacy and fear of childbirth. Improvements in depression, mindfulness, and birth outcome expectations were underpowered. At postnatal follow-up significant improvements were found in anxiety, whereas improvements in mindfulness, stress, and fear of birth were significant at a less conservative alpha level. Discussion: This pilot study demonstrated that a blended mindfulness and skills-based childbirth education intervention was acceptable to women and was associated with improvements in women’s sense of control and confidence in giving birth. Previous findings that low self-efficacy and high childbirth fear are linked to greater labor pain, stress reactivity, and trauma suggest the observed improvements in these variables have important implications for improving maternal mental health and associated child health outcomes. Ways in which these outcomes can be achieved through improved childbirth education are discussed.